MODAL SOSIAL MASYARAKAT PETANI KOPI DI KABUPATEN ACEH TENGAH - Saputra, Akmal; Sopar, Sopar; Ainun, Nur; Hasanah, Uswatun (Sociology Department Of Syiah Kuala University, 2023)
Central Aceh is an area that has the potential of coffee farming in Aceh. This research provides an important overview of local values and social capital in coffee farming communities in Central Aceh District. The research explains how the coffee farming community can continue to survive from the colonial era to post-peace, the survival of coffee farmers in Central Aceh Regency is not just understood for economic gain alone, but there are local values carried by the coffee farming community in Central Aceh Regency. This research uses qualitative methods by using data collection techniques through observation, in-depth interviews, documentation and also FGDs. Observations were conducted to observe the activities of coffee farmers in Central Aceh Regency, especially how farming communities build networks between farmers, how norms are built by coffee farmers. Then, in-depth interviews were conducted by interview some informants: coffee farmers and Reje. In addition, documentation can be in the form of data from the local government related to coffee plantations. Furthermore, FGDs were also conducted to find important information about social capital. Based on the results of the research data analysis, it can be found that the social capital of coffee farming communities in Central Aceh Regency can be classified into three, namely: first: trust; second: social norms which include gotong royong, religion, knowledge, participation and tolerance; and third: social networks which include Reje Atu Lintang Forum, Sarah Opat Institution, Reje Genap Mupakat (RGM), Keujruen Blang, Pengulu Uteun, Assistance Workers and BUMK. An interesting finding is that social capital is present in a multicultural society so that it has a good impact on the sustainability of coffee plantations in Central Aceh District.